(untitled) - Martinez, Jose L. (Boca Raton, FL, 2008)
Supercritical fluid (SCF) technology is an alternative to traditional solvents for extraction, fractionation, and isolation of active ingredients. The aim of this book is to present the current state of the art in extracting and fractionating bioactive ingredients by SCFs. Each chapter reviews the major active components of a target material, including chemical, physical, nutritional, and pharmaceutical properties, then analyzes the specific SCF process used for the target material, compares traditional processing methods versus SCF technology, and offers conclusions with supporting data. A review of the fundamentals of the technology and an examination of SCF extraction systems and process economics are also included. The readership for the book includes food scientists, technologists, and engineers, as well as other professionals interested in the nutraceutical and functional food sector. The editor is affiliated with Thar Technologies, Inc
Keywords: Supercritical fluid extraction,Functional foods,Bioactive compounds,Kỹ thuật sinh học